ChemInform Abstract: In situ Analyses for Ion Storage Materials. Issue 47 (3rd November 2016) - Yang, Junghoon; Muhammad, Shoaib; Jo, Mi Ru; Kim, Hyunchul; Song, Kyeongse; Agyeman, Daniel Adjei; Kim, Yong‐Il; Yoon, Won‐Sub; Kang, Yong‐Mook
Abstract: Review: such as x‐ray and neutron diffraction, x‐ray absorption spectroscopy, and microscopy; 222 refs.